Beyond National Sovereignty: Filippo Vassalli on Mission to London (1945) (Italian Review of Legal History, 2022)
In November-December 1945, the civil lawyer Filippo Vassalli undertook a mission to London, at the head of a delegation of jurists invited by the British Council to observe the functioning of the English institutions, through a “legal sightseeing” made up of talks and meetings with illustrious exponents of British politics and legal culture. Some documents from the Vassalli archive now allow us to delve into the implications of this journey, of which the jurist wrote an account in some of his essays. The research, in particular, aims to demonstrate that during the mission Vassalli developed the idea of overcoming the myth of national sovereignty in the international area. Later, he extended this vision to the field of civil law. Vassalli supported the orientation favorable to the creation of an organization superior to individual States, which would ensure peace in the world and offer supranational protection of human rights. The mission also had consequences for the system of justice, the police and Italian economic life, on the eve of the Constituent Assembly, in which Vassalli did not take part. As head of the mission, he delivered to Alcide de Gasperi, Italian Minister of Foreign Affaris, a message from Foreign Secretary Ernest Bevin, an eminent figure in British politics, who had already influenced Vassalli in the field of the future structure of international relations in peacetime. The mission to London, consequently, represents a central event for understanding Vassalli’s thought in the first republican decade.
Keywords: National Sovereignty; Supranational Sovereignty; Human Rights; United Nations Organisation (ONU); Vassalli, Filippo; De Gasperi, Alcide; Bevin, Ernest; Eden, Anthony